RBM14 Modulates Tubulin Acetylation and Regulates Spindle Morphology During Meiotic Maturation in Mouse Oocytes - Qin, Hao; Qu, Yi; Yuan, Yi-Feng; Li, Yang-Yang; Qiao, Jie (Frontiers in Cell and Developmental Biology, 2021)
RBM14 is an RNA-binding protein that regulates spindle integrity in mitosis; however, its functions during meiosis are still unclear. In this study, we discovered that RBM14 expression was down-regulated in oocytes from old mice. The RBM14 distribution at different stages of meiosis was explored, while it presents overlapped localization patterns with α-tubulin in MI- and MII-stage oocytes. Treatment of MI-stage oocytes with spindle-perturbing agents revealed that RBM14 was co-localized with microtubules. RBM14 knockdown with RBM14-specific morpholino showed that RBM14-depleted oocytes underwent symmetric division compared to the controls. RBM14 knockdown also resulted in spindle defects and chromosome abnormalities during oocyte maturation, presumably due to α-tubulin hyperacetylation. Co-immunoprecipitation analysis demonstrated that RBM14 is interacted with endogenous α-tubulin in mammalian cells. These findings indicate that RBM14 is an essential modulator of oocyte meiotic maturation by regulating α-tubulin acetylation to affect spindle morphology and chromosome alignment. Consequently, RBM14 represents a potential biomarker of oocyte quality and a novel therapeutic target in women with oocyte maturation failure.